Diversity in Phenotypes Associated With Host Persistence and Systemic Virulence in Streptococcus sanguinis Strains - Alves, Livia A.; Salvatierra, Geovanny C.; Freitas, Victor A.; Höfling, José F.; Bastos, Débora C.; Araujo, Thaís L. S.; Mattos-Graner, Renata O. (Frontiers in Microbiology, 2022)
Streptococcus sanguinis is a pioneer commensal species of dental biofilms, abundant in different oral sites and commonly associated with opportunist cardiovascular infections. In this study, we addressed intra-species functional diversity to better understand S. sanguinis commensal and pathogenic lifestyles. Multiple phenotypes were screened in nine strains isolated from dental biofilms or from the bloodstream to identify conserved and strain-specific functions involved in biofilm formation and/or persistence in oral and cardiovascular tissues. Strain phenotypes of biofilm maturation were independent of biofilm initiation phenotypes, and significantly influenced by human saliva and by aggregation mediated by sucrose-derived exopolysaccharides (EPS). Production of H2O2 was conserved in most strains, and consistent with variations in eDNA production observed in few strains. Diversity in complement C3b deposition correlated with rates of opsonophagocytosis by human PMN and were influenced by culture medium and sucrose-derived EPS in a strain-specific fashion. Differences in C3b deposition correlated with strain binding to recognition proteins of the classical pathway, C1q and serum amyloid protein (SAP). Importantly, differences in strain invasiveness into primary human coronary artery endothelial cells (HCAEC) were significantly associated with C3b binding, and in a lesser extent, with binding to host glycoproteins (fibrinogen, plasminogen, fibronectin, collagen). Thus, by identifying conserved and strain-specific phenotypes involved in host persistence and systemic virulence, this study indicates potential new functions involved in systemic virulence and highlights the need of including a wider panel of strains in molecular studies to understand S. sanguinis biology.